KOMUNIKASI PEMBANGUNAN: REMBUK WARGA TENTANG MUSRENBANG GUNA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Aditya, Krisna (KOMUNIKA BANGSA, 2025)
The RW16 Jatihandap Residents Consultation is a development communication forum that aims to improve community welfare and infrastructure. Musrenbang (Develoment Planning Conference) is a development planning process that involves the community. The aim of this research is to analyze the role of the Jatihandap RW16 Residents’ Consultation in improving community welfare and infrastructure through the 2025 Musrenbang. This research uses qualitative methods with data collection and observation techniques. Data were analyzed using thematic analysis techniques. The research results show that the RW16 Jatihandap Residents’ Consultation has an important role in improving community welfare and infrastructure through the 2025 Musrenbang. Effective development communication and community participation in the Residents’ Consultation and Musrenbang can increase community awareness and involvement in development.